O efeito da diversificação na mineração - Bonança, Marcelo (2014)
This study analyses the effects of diversification in risk and return among the major global mining players. To evaluate the diversification, firstly, we created a ranking that relates risk, degree of diversification and return of the companies. It was mandatory to create a data base with a series of revenues and proxies of cash generation by business, which is not fully provided by Bloomberg, Economática or other public data bases. We estimated the effects of diversification by using the CAPM to calculate the companies’ beta and basic statistics of the historical return series to find the Sharpe Index. We looked through the financial statements to understand more profoundly their businesses for a sample equivalent to 50% of the market capitalization of the top 100 mining companies of the world for the period from 2002 to 2014. Finally, we approached, as a study case, essential issues in the diversification as efficiency and discipline in capital allocation. Our study confirmed the presence of a negative correlation between risk and diversification degree. It also showed evidences which suggest that focused companies have better discipline in capital allocation, and hence, generate more value to their shareholders.